Transformando frequências em melodias: análise de ondas sonoras e da curva de Railsback - Martinez, Cristiane Aparecida Pendeza; Magalhães, Gustavo de Freitas; Martinez, André Luís Machado (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2024)
This paper investigates the principles of acoustics and musical language, with an emphasis on the transformation of frequencies into melodies through the piano. The study focuses on the analysis of the Railsback tuning curve, applied by piano technicians to optimize sound quality. Using the MATLAB programming environment, we examine in detail various waveforms, including sinusoidal, square and triangular, to analyze their characteristics and effects on sound synthesis. We implement an algorithm that incorporates the Railsback curve to adjust the frequencies of the keys of a piano, allowing the reproduction of music with harmonious acoustic balance.